Marigold Flower (Tagates erecta L.) as a Natural Yellow Food Colorant: Extraction Optimization and Stability Assessment - Mukmin Sapto Pamungkas; Daffa Rafli Afrizal; Edia Rahayuningsih; Meiga Putri Wahyu Hardhianti; Rini Dharmastiti (Lembaga Penelitian dan Pengabdian Masyarakat AKIPBA, 2026)
Marigold flowers (Tagetes erecta L.) are especially rich in carotenoids and are widely used as natural yellow food colorants. Previous studies on extracting carotenoids from marigolds mainly relied on single-factor methods, with limited focus on variable interactions or extract stability. This study aimed to optimize extraction conditions using response surface methodology and to assess the stability of the carotenoid extract during storage with commercial salt and sugar. Following four days drying of fresh marigold flower petals in the laboratory with air convection, extraction was carried out using either a Soxhlet extractor or a three neck round bottom flask (extraction). The total amounts of flavonoids, phenolics, and carotenoids in the fresh flower material were determined initially by using visible spectroscopy. A Central Composite Design (CCD) with a two-factor interaction (2FI) model was used to optimize extraction conditions, considering three variables: pH, temperature, and time. The coefficient of determination (R2) was 80.25%. The best extraction conditions were pH 5.9, 62.9 °C, and 67.1 minutes, resulting in a TCC of 3490 mg/100 g DW with a desirability of 1.000. Carotenoids showed greater stability in the presence of 2% citric acid or 3% salt, while 3% sugar reduced stability during 76 hours of storage.